Bone Mineral Density in Thalassemia Major Patients from Antalya, Turkey - Ibrahim Aslan; Duran Canatan; Nihal Balta; Gulizar Kacar; Cengaver Dorak; Ahmet Ozsancak; Nurgul Oguz; Ruya Cosan (International Journal of Endocrinology)
Aim. We assessed the bone mineral density and related parameters in nine adults, thirty-eight pubertal, prepubertal totally forty-seven patients with thalassemia major living in Antalya, Turkey. Materials and Methods. We measured height and pubertal staging in last five years by six-month intervals. Average ferritin and hemoglobin concentrations were calculated for last three years. The levels of hydroxyproline, calcium, phosphorus, and creatinine were measured in 24 h urine, and those of parathormone, IGF 1, osteocalcine, alkaline phosphatase, calcium, ionized calcium, magnesium, phosphorus, creatine, blood glucose, thyroid stimulating hormone, alanine transaminase, and aspartate transaminase were determined in serum, and also the bone mineral density was measured. Results. The average L1–L4 bone mass density was 27.1±10.1 g cm−2; the average bone mineral content was 0.65 ± 0.11 g. of the patients with a Z-score under 2.5. A moderate relationship was found between the bone mass density age and height. Subjects in low pubertal staging and short stature (<3% percentile) have significantly lower bone mass densities P<0.001. Conclusion. he prevalence of osteoporosis is high in patients with thalassemia major, possibly related to delayed puberty.